A infidelidade virtual no relacionamento amoroso: correlatos afetivos e sociais - Coutinho, Márcio de Lima (2013)
This thesis aimed at investigating the social and affective correlates of romantic relationships. It has emphasis on virtual infidelity. This study was theoretically and methodologically carried out by using the theoretical contributions of tetrangular model of love and human values. It also counted on the studies about romantic jealousy and the addiction to the Internet. In order to achieve the aim of this thesis it was necessary to develop three studies: the first characterized as preliminary and instrumental was aimed at adapting/validating two instruments; the virtual infidelity scale and the Internet addiction scale for the Brazilian context. The participants were 246 college students from public and private educational institutions of João Pessoa, PB; with age range of 17-55 years old (mean = 24.3, SD = 7.15), most of them were female (62.1%). The results obtained by the Exploratory Factor Analysis of the virtual infidelity scale revealed two dimensional structures: sexual relationship (α = 0.96) and friendship relationship (α = 0.81). The results of the measurement addiction to the Internet indicated a one-dimensional structure (α = 0.89). The Study 2 was aimed at confirming the factor structure of the scales applied in the first study and verify the strength of correlations with the constructs love, jealousy and human values. A number of 210 university students were the participants who answered the same scales from Study 1, added to the measures: tetrangular love, romantic jealousy and the questionnaire of the basic values. These participants ages ranged from 17 to 50 years (M = 23.6, SD = 6.41) mostly were female (73.8%). The results obtained by the Confirmatory Factor Analysis (CFA) of virtual infidelity and addiction to the Internet for the Brazilian context suggested that the model with four and three dimensions, respectively which was originally proposed by the authors, was the one that best showed adequated validity and accuracy (GFI = 0.89, CFI = 0.97 and GFI = 0.83, CFI = 0.96). Concerning the predictive strength of the measures: addiction to Internet, jealousy, love and human values it was observed that the first variable contributed significantly to the explanation of the attitudes towards virtual infidelity (R = 0.25, p <0.001), the second variable romantic jealousy showed a marginal contribution (R = 0.30, p = 0.05), the third independent variable, love, did not have a significant contribution (R = 0.34, p> 0.05), and, lastly, the human values had a prominent contribution (R = 0.49, p <0.001).The third study aimed to developing a theoretical model to explain the constructs based on the human values, jealousy and addiction to the Internet was carried out to explain attitudes towards virtual infidelity. The participants were 204 Internet users, with age range of 17 to 66 years (M = 29.3, SD = 10.34), mostly female (59.8%). The results of the statistical analyzes indicated that the three constructs were fundamental for explaining the attitudes toward virtual infidelity. Concerning the human values (r = -0.15, p <0.05) the results brought out the sub functions experimentation, suprapersonal, existence, normative and realization, the romantic jealousy (r = -0.33, p <0.001) with dimensions not threatening,, exclusion and addiction to Internet (r = 0.13, p <0.05) with dimensions withdrawal and social problems, time management and performance and replaced reality were underlying components facing the attitudes toward virtual infidelity. Based on these findings it may be inferred that the results contributed satisfactorily with the explanatory model of behavior about the virtual infidelity. It is also expected that these results may be applied in future researches.